Ecological Transitions and the Shape of the Decapod Tree of Life. (24th May 2022) - Davis, Katie E; De Grave, Sammy; Delmer, Cyrille; Payne, Alexander R D; Mitchell, Steve; Wills, Matthew A
Synopsis: Understanding the processes that shaped the distribution of species richness across the Tree of Life is a central macroevolutionary research agenda. Major ecological innovations, including transitions between habitats, may help to explain the striking asymmetries of diversity that are often observed between sister clades. Here, we test the impact of such transitions on speciation rates across decapod crustaceans, modeling diversification dynamics within a phylogenetic framework. Our results show that, while terrestrial lineages have higher speciation rates than either marine or freshwater lineages, there is no difference between mean speciation rates in marine and freshwater lineages across Decapoda. Partitioning our data by infraorder reveals that those clades with habitat heterogeneity have higher speciation rates in freshwater and terrestrial lineages, with freshwater rates up to 1.5 times faster than marine rates, and terrestrial rates approximately four times faster. This averaging out of marine and freshwater speciation rates results from the varying contributions of different clades to average speciation rates. However, with the exception of Caridea, we find no evidence for any causal relationship between habitat and speciation rate. Our results demonstrate that while statistical generalizations about ecological traits and evolutionary rates are valuable, there are many exceptions. Hence, while freshwater and terrestrial lineages typically speciate faster than their marine relatives, there are many atypically slow freshwater lineages and fast marine lineages across Decapoda. Future work on diversification patterns will benefit from the inclusion of fossil data, as well as additional ecological factors.